Sprint performance determinants in high level young swimmers - Matos, Carolina L. (2022)
Background The identification and evaluation of the variables that influence performance have been essential to obtain excellence in sport. Objective The aim of this study was to identify which parameters have the most influence on the 50 meters freestyle time, in young competitive swimmers. Methods One hundred and eighty-four high-level swimmers (males, n=92: 14.60±0.56 years; females, n=92: 13.53 ± 0.54 years) with 468±66 FINA points in the 50 meters freestyle in short course participated in this study. Age, height, body mass, wingspan, stroke rate, stroke length, stroke index, turning time (5 m + 10 m), horizontal jumping, and medicine ball throwing were assessed. The swimming performance was assessed in a 50 meters freestyle time-trial at maximum speed in a 25 meters swimming pool. A multiple regression was performed to assess the relationship between one dependent variable (50 meters freestyle time) and independent variables. Results The results showed differences between both genders. In male swimmers, only the turning time and the horizontal jump were significant (r ² =0.8819; p<0.001), whilst the females, besides the same variables, presented the height, body mass, stroke length and stroke index (r ² =0.9013; p<0.01). Conclusion In conclusion, in young male swimmers, the turning time and the horizontal jump contributed significantly to the 50 meters freestyle swimming performance, and in young female swimmers, the main contributors were the turning time, horizontal jump, height, body mass, stroke length and stroke index.